Analysis Of Relationship Between Readiness And Attitude Levels Of Vocational School Students For Online Learning In Terms Of Several Variables In The Process Of Covid 19 Pandemic - Gömleksiz, Mehmet Nuri; Pullu, Emine Kübra (T.C. Milli Egitim Bakanligi, 2020)
The aim of this study is to determine the relationship between readiness and attitude levels of vocational school students for online learning in terms of several variables in the process of Covid 19 pandemic. Study group includes students enrolled at a vocational school of a university located in Central Anatolia Region in Turkey. ‘Online Learning Readiness Scale’ and ‘Attitude Scale for Online Learning’ were used to collect the data. The scales were administered on a total of 312. The study included 264 female and 48 male students. Kolmogorov-Smirnov normality test was used to see whether the data were normally distributed. Independent groups t test was used to determine the differences in terms of gender, grade level, technology use level and internet quota variables while One Way ANOVA was used to see the differences in terms of the variables of department nd technological device to connect the system. Pearson Correlation Coefficient test was used to measure the strength and the direction of relationship between readiness and attitude levels of vocational school students for online learning. Study results revealed a positive relationship between the readiness and attitude levels of the students for online learning. © 2020. All Rights Reserved.
Keywords: attitude; Covid 19; Online learning; pandemic; readiness